Onion and garlic keep us healthy - Gorrepati, Kalyani; Khade, Yogesh P. (Indian Horticulture, 2019)
Onion and garlic not only add specific taste and flavour to food but also contribute for good health. Onions are rich in bioactive components that offer numerous health benefits. Onions also contain flavonoids (especially quercetin), dietary fiber, and organosulfur compounds (OSCs). Onion is one of the richest known sources of flavonoids. Two types of flavonoid subgroups are present in onion, viz. anthocyanins and querectin. Quercetin is a potent antioxidant flavonoid. Quercetin is mainly available in the upper skin and near the skin layers. On the other hand, garlic contains amino acid alliin, which is responsible for its pungent odour and taste. When garlic is chopped or crushed, allinase enzyme activates thereby producing allicin from alliin. Enzyme allinase acts upon cystosolic cystein sulfoxide forming sulfenic acid. Sulfenic acid further rapidly condenses to form allicin. Garlic contains several sulfur containing compounds that are used as bases in the preparation of pharmacological products. Allicin is the principal bioactive sulfur compound present in garlic.